What determines the accessibility of early childhood education in Bangladesh? - Md. Tuhin Ahmed; Sayed Arafat Zubayer (Springer, 2024)
Abstract This paper aims to understand the potential factors influencing the accessibility of early childhood education (ECE) in Bangladesh. Utilising data from the Multiple Indicator Cluster Survey (MICS) 2019, this study explored the influence of individual, household, socio-economic as well as geographical variables on ECE enrollment. It employed a comprehensive approach, which involved using descriptive statistics for univariate analysis, chi-square and t-statistics for bivariate analysis, and the logit model for multivariate analysis. The findings revealed that a child's likelihood of attending an ECE program increases with their age, while those with functional difficulties and larger household sizes exhibit lower odds of attendance. Children with mothers possessing higher education levels demonstrated increased odds of ECE enrollment. Wealthy households and urban or Mymensingh division residency were associated with higher odds of ECE enrollment, while Barishal, Rajshahi, and Sylhet divisions indicated lower odds. To enhance ECE accessibility, the study recommends implementing a roadmap for ensuring universal early childcare and early education with an emphasis on socioeconomically underprivileged children, particularly in rural areas. Proposed strategies may include providing financial assistance to poor households and fostering public-private partnerships for ECE provision in remote regions like Barishal, Rangpur, Rajshahi, and Sylhet divisions. Moreover, it is crucial to make parents and communities aware about the significance of ECE in order to make sure that children ages 3-5 years are involved in ECE programs.